Improving of the wear resistance of working parts agricultural machinery by the implementation of the effect of self-sharpening - Aulin, Victor; Warouma, Arifa; Lysenko, Sergei; Kuzyk, Alexander (International Journal of Engineering and Technology, 2016)
The failure of the cutting elements of farm machinery is due to the blunting of cutting edges (increase of their radius) till the limit values. The most effective method for increasing the wear resistance of farm machinery is the realization of self-sharpening effect of the cutting elements. The testings took place in laboratory and field at the State Technical University of Kirovograd (Ukraine) in 2015. The technical equipment consists of the consolidated farmer plowshares by different methods as well as their samples, devices for measuring the wear resistance and thumbprint plowshares. It was determined the resistance to wear, the radius of curvature and the changing coefficient of the blades shape. The self-sharpening process was examined throughout the experiment. The results showed that the consolidated plowshares by the proposed technology (laser welding of the mixture (PS-14-60 + 6% В4С) compared to the traditional technology (volumetric heat treatment) have a blade radius 2.5 times lower, a wear 2.2 to 2.78 times lower and the self-sharpening process of the plowshares has been observed since the beginning of the wear until the time limit operation. The changing shape coefficient was respectively of 0.98 for the consolidated plowshares with alloy PS-14-60 + 6% B4C and 0.82 for those consolidated by volumetric heat treatment.